2022
DOI: 10.2486/indhealth.2021-0222
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between using tables, chairs, and computers and improper postures when doing VDT work in work from home

Abstract: This study focused on everyday furniture and computers used in work from home and aimed to investigate how improper postures increase the risk of musculoskeletal disorders using different combinations of tables, chairs, and computers. Twenty-one healthy participants were asked to perform a visual display terminal task for 30 minutes in a laboratory modeled on the work from home concept. Seven experimental conditions were set up according to the different combinations of desks, chairs, and computers. Three-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…After conducting a study on working postures in VDT work with various furniture including floor chair, floor cushion, and sofa, results showed that the neck flexion angle when using a sofa and a floor cushion was significantly larger when compared with using a dining chair. 10 Specifically, the neck angle created when using a sofa was in the critical zone of the ISO 11226 standard. 17 The poor posture on using sofas and floor cushions may explain the high risk of mild neck/shoulder pain in the WFH setup.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…After conducting a study on working postures in VDT work with various furniture including floor chair, floor cushion, and sofa, results showed that the neck flexion angle when using a sofa and a floor cushion was significantly larger when compared with using a dining chair. 10 Specifically, the neck angle created when using a sofa was in the critical zone of the ISO 11226 standard. 17 The poor posture on using sofas and floor cushions may explain the high risk of mild neck/shoulder pain in the WFH setup.…”
Section: Discussionmentioning
confidence: 99%
“…However, the neck flexion angle of using a laptop computer was suggested to be in the critical range of neck pain only in a setup without a proper desk. 10 Besides, using an adjuster to elevate the screen height and modify the keyboard location of a laptop computer was reported to reduce the neck flexion angle and relative muscle activities. 21 No significant association between computers and neck pain or low back may be due to part of the participants in the present study using proper furniture and adjusters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations